An approach to sense pheromone concentration by pre‐concentration and gas sensors. Issue 5 (22nd April 2013) - Wehrenfennig, Christoph; Schott, Matthias; Gasch, Tina; Meixner, Daniel; Düring, Rolf‐Alexander; Vilcinskas, Andreas; Kohl, Claus‐Dieter
Abstract In this investigation we combined enrichment with different analysis techniques for in situ sensing of the pheromone main component of the European Grapevine Moth (Lobesia botrana). The electroantennographic detection (EAD) offers the lowest in situ detection limit, but has a limited lifetime of only few hours. Based on the enrichment it is possible to pre‐concentrate the natural pheromone level up to a threshold for biomimetic analytic systems. By metal‐oxide semiconductor gas sensors in a 'selective odorant measurement of a multi‐sensor array' (SOMMSA) setup it is possible to achieve a system with a suitable lifetime for monitoring applications. Due to the sequential desorption from the enrichment material with increasing temperature steps it is possible to eliminate interfering gas components and therefore increase the selectivity of the complete system and to achieve a tool for monitoring applications, e.g. in a vineyard. <inline-graphic xlink:href="ark:/27927/pgg20q11tfw" content-type="pssa201200784-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />